NHERITANCE OF EXTERNAL GENETIC CHARACTERISTICS IN CHICKEN THROUGH TRIPLE CROSSING MODEL - Safriyanto Dako, Fahrul Ilham, Nibras. K. Laya, Frida. M Yusuf (International Journal of Advanced Science and Technology, 2020)
Background and objective: The external genetic inheritance in chickens is very important to know because as a basis for the development of pure race, commercial, and the formation of uniformity in coat color. The purpose of this study was to determine the Inheritance pattern of characteristic external genetic in chicken through the triple crossing model. Materials and methods: Chicken mating uses three types of chickens, namely: Kampung Chicken (K), Broiler Chicken (B), and Leghorn Chicken (L). A total of 257 cross hens were observed from four genetic groups: K♂ x B♀; K♂ x L♀; KB♂ x KL♀; KL♂ x KB♀. External genetic characteristics observed included feather color, feather color pattern, fur pattern, flicker fur, shank color, and comb shape. Results:External Genetic Characteristics of chickens through the triple crossing model resulted in the External Genetic Constitution in KLB and KBL chickens (generation F2) is iiee ss pp IdId and there are six combination of feather color patterns produced namely Black (E_), Colombian (ee), Wyandotte Columbian (ee), brown/light brown (eb), dark brown (edb), and wild (e+). The average Heterozygosity of expectations per individual (H) for Genes of External Characteristic in KLB chickens is0.39428±0.118, and KBL chickens amounted to 0.38074±0.1136. Conclusion: External Genetic Characteristics of chickens through the triple crossing model produce six combinations of feather color patterns which meets the Hardy-Weinberg balance, with External Genetic Constitution (KBLand KLB chicken) in the F2 generation are ii ee ss pp, IdId that have the gene diversity is 0.38074 ± 0.1136 (KBL) - 0.39428 ± 0.118 (KLB). Background and objective: The external genetic inheritance in chickens is very important to know because as a basis for the development of pure race, commercial, and the formation of uniformity in coat color. The purpose of this study was to determine the Inheritance pattern of characteristic external genetic in chicken through the triple crossing model. Materials and methods: Chicken mating uses three types of chickens, namely: Kampung Chicken (K), Broiler Chicken (B), and Leghorn Chicken (L). A total of 257 cross hens were observed from four genetic groups: K♂ x B♀; K♂ x L♀; KB♂ x KL♀; KL♂ x KB♀. External genetic characteristics observed included feather color, feather color pattern, fur pattern, flicker fur, shank color, and comb shape. Results:External Genetic Characteristics of chickens through the triple crossing model resulted in the External Genetic Constitution in KLB and KBL chickens (generation F2) is iiee ss pp IdId and there are six combination of feather color patterns produced namely Black (E_), Colombian (ee), Wyandotte Columbian (ee), brown/light brown (eb), dark brown (edb), and wild (e+). The average Heterozygosity of expectations per individual (H) for Genes of External Characteristic in KLB chickens is0.39428±0.118, and KBL chickens amounted to 0.38074±0.1136. Conclusion: External Genetic Characteristics of chickens through the triple crossing model produce six combinations of feather color patterns which meets the Hardy-Weinberg balance, with External Genetic Constitution (KBLand KLB chicken) in the F2 generation are ii ee ss pp, IdId that have the gene diversity is 0.38074 ± 0.1136 (KBL) - 0.39428 ± 0.118 (KLB).